Pengembangan Modul Ajar Pendidikan Agama Islam Berbasis Karakter Bangsa Nilai Komunikatif - Fajrul Laili Zuhriyyah; Machnunah Ani Zulfah; Muhammad Fodhil; Chusnul Chotimah (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
This research focuses on the development and testing of a character-based Islamic Religious Education (PAI) teaching module, particularly on communicative values ??through social media etiquette. The background is the importance of instilling religious values ??and character in the digital era, where social media is massively used by students. The goal is to equip students with digital communication ethics, prevent the spread of negative content, and foster polite and responsible attitudes, in line with strengthening the nation's religious and cultural character. The method used is Research and Development (R&D) with the 4D model (Define, Design, Develop, Disseminate). The subjects of this study were PAI teachers and 11th-grade students of SMAN 1 Jombang. The results showed that this teaching module was very suitable for use based on the assessment of expert validators. This is evidenced by the N-Gain value of 0.77, which is included in the high category. In addition, the effectiveness of the pre-test also showed a figure of 77.2%, which indicates that this module is effective. In conclusion, this teaching module is an innovative solution to shape strong and responsible student characters amidst the rapid development of information technology.